Use and increase the effectiveness of innovative pedagogical methods in education - Mardonova F.Yu. (Zien Journals, 2022)
When using interactive methods in the educational process, the teacher acts as a controller of the educational process, while the goal of management is focused on the student as an object and subject of learning. Consequently, the pedagogical technology of the content of education arises on the basis of methods, forms and means. This process is aimed at achieving a guaranteed result
Keywords: pedagogical technology; innovation; integration; technological approach